CMET-47. CLINICAL EVALUATION OF FITNESS TO DRIVE IN PATIENTS WITH BRAIN METASTASES. (5th November 2018) - Valencia-Sanchez, Cristina; Schild, Steven; Vora, Sujay; Ashman, Jonathan; Daniels, Thomas; Halyard, Michele; Rule, William; Zhang, Nan; Butterfield, Richard; Sharma, Akanksha; Mrugala, Maciej; Porter, Alyx
Abstract: INTRODUCTION: Brain tumors can result in focal neurological and cognitive deficits which may impair the ability to drive. There are no evidence-based recommendations on driving restrictions for patients with brain metastases. Recommendations vary per practice, with extrapolation based on local driving and epilepsy laws. Occupational Therapy driving assessment (OTDA) may provide insight into limitations for this population. OBJECTIVE: To determine whether clinical neurologic examination is sufficient to predict suitability to drive in patients with brain metastases. METHODS: We assessed the concordance between Neurology assessment of suitability to drive (pass/fail) and OTDA in individuals with brain metastases. 40 subjects were prospectively enrolled. Neurooncology evaluation was performed as standard of care, including an interview and neurological examination. Subjects subsequently underwent OTDA during which a battery of objective measures of visual, cognitive and motor skills related to driving was administered. RESULTS: Preliminary results from the first 29 patients included are reported. Mean age was 68 years. Lung was the primary location of the tumor in 62% cases. More patients in the group that failed OTDA had bilateral brain metastasis (77.3% vs 42.9%, p=0.0478). The sensitivity of the Neurology assessment to predict driving fitness compared to OTDA was 22.7% and the specificity 71.4%. The 22 patients who failed OTDA were more likely to fail on Vision Coach (81.8%), MOCA (68.2%) and Trail Making (50%) tests. DISCUSSION: There was poor correlation between the assessment of suitability to drive by Neurology and the outcome of the OTDA in patients with brain metastases. Subtle deficits that may impair the ability to drive safely may not be evident on neurologic examination. The Vision Coach, MOCA and Trail Making tests were the most sensitive tests to predict driver safety. The results raise questions about the choice of assessments in making recommendations about fitness to drive in people with brain metastases.